Social support following a natural disaster: A longitudinal study of survivors of the 2013 Lushan earthquake in China. (March 2019) - Shang, Fanhong; Kaniasty, Krzysztof; Cowlishaw, Sean; Wade, Darryl; Ma, Hong; Forbes, David
Highlights: Greater quality of support received predicted lower levels of symptoms of posttraumatic stress and psychological distress. Quantity of received social support did not predict of symptoms of posttraumatic stress or psychological distress. These results were still robust when controlled for gender, negative life events and family financial status. What appears to be critical in the process of supporting disaster survivors is the quality, not necessarily the quantity, of support provided. Abstract: The idea that social support post-disaster is beneficial to survivors' mental health is widely accepted by both researchers and practitioners. However previous social support studies are mainly focused on perceived social support, and the limited received social support studies have produced mixed results. In this study we modelled the influence of both quantity and quality of received social support on long-term mental health outcomes in a longitudinal study of 2013 Lushan earthquake survivors in China. Survivors were invited to complete a questionnaire interview 7 months after the earthquake and were followed up 31 months later ( n  = 161). Hierarchical regression analyses that controlled for disaster exposure variables showed that greater quality of social support received 7 months after disaster predicted lower levels of posttraumatic stress symptoms and psychological distress two years later, however quantity of received social support was not significant in predicting these two outcomes. These results remained robust when controlled for gender, negative life events and family financial status. The findings of this study suggest that what appears to be critical in the process of supporting disaster survivors is the quality, not necessarily the quantity, of support provided.